Frustrated magnetism in the spin–chain metal Yb2Fe12P7. (8th January 2016) - Baumbach, R E; Hamlin, J J; Janoschek, M; Singleton, J; Maple, M B
Abstract: Magnetization measurements for magnetic fields up to 60 T are reported for the noncentrosymmetric spin–chain metal Yb2 Fe12 P7 . These measurements reveal behavior that is consistent with Ising-like spin chain magnetism that produces pronounced spin degeneracy. In particular, we find that although a Brillouin field dependence is observed in M ( H ) for with a saturation moment that is close to the expected value for free ions of Yb 3+  , non-Brillouin-like behavior is seen for with an initial saturation moment that is nearly half the free ion value. In addition, hysteretic behavior that extends above the ordering temperature is seen for but not for, suggesting out-of-equilibrium physics. This point of view is strengthened by the observation of a spin reconfiguration in the ordered state for which is only seen for and after polarizing the spins. Together with the heat capacity data, these results suggest that the anomalous low temperature phenomena that were previously reported (Baumbach 2010 et al Phys. Rev. Lett .105 106403) are driven by spin degeneracy that is related to the Ising-like one dimensional chain-like configuration of the Yb ions.